2021
DOI: 10.3389/fphar.2021.734613
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Drugs-Related Neuroprotection as a Potential Therapeutic Tool Against Chemotherapy-Induced Cognitive Impairment

Abstract: In recent years, and particularly associated with the increase of cancer patients’ life expectancy, the occurrence of cancer treatment sequelae, including cognitive impairments, has received considerable attention. Chemotherapy-induced cognitive impairments (CICI) can be observed not only during pharmacological treatment of the disease but also long after cessation of this therapy. The lack of effective tools for its diagnosis together with the limited treatments currently available for alleviation of the side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 143 publications
0
7
0
Order By: Relevance
“…As mentioned previously, a mice study found that CBD is protective against paclitaxel-induced neurotoxicity and in a separate experiment, found that CBD did not reduce the paclitaxel-induced inhibition of breast cancer cell viability [ 190 ]. Boullon and colleagues’ review suggests the potential for cannabinoids to address chemotherapy-induced cognitive impairment, given evidence of cannabinoids for the modulation of neuroinflammation and oxidative stress in different pathologies with a similar cognitive phenotype to CICI [ 199 ].…”
Section: Combining Cbd With Orthodox Cancer Treatmentmentioning
confidence: 99%
“…As mentioned previously, a mice study found that CBD is protective against paclitaxel-induced neurotoxicity and in a separate experiment, found that CBD did not reduce the paclitaxel-induced inhibition of breast cancer cell viability [ 190 ]. Boullon and colleagues’ review suggests the potential for cannabinoids to address chemotherapy-induced cognitive impairment, given evidence of cannabinoids for the modulation of neuroinflammation and oxidative stress in different pathologies with a similar cognitive phenotype to CICI [ 199 ].…”
Section: Combining Cbd With Orthodox Cancer Treatmentmentioning
confidence: 99%
“…Although it cannot be discarded that other treatments received by the cancer patients (opiates, neuroleptics) and other confounders, like inadequate nutritional status, may contribute to the problem, preclinical in vitro and in vivo studies do support that chemotherapy causes brain neurotoxicity ( Rzeski et al, 2004 ; Matsos and Johnston, 2019 ; Boullon et al, 2021 ; Bagues et al, 2022 ). Indeed, currently, chemofog is hypothesized to be the result of neuronal injury with abnormal brain remodeling.…”
Section: Central Neurotoxicity: Chemobrainmentioning
confidence: 99%
“…The occurrence of CICI (chemobrain) has been demonstrated in both preclinical models and patients and different biological mechanisms may contribute. As shown above, the ECS is implicated in at least two of the biological mechanisms in which chemotherapeutic drugs are thought to induce CICI, that is, neuroinflammation and oxidative stress (Boullon et al , 2021). Importantly, several reports have pointed out that pharmacological modulation of the ECS is able to reverse cognitive impairments in neuropathologies in which these mechanisms are involved, such as AD, PD and TBI.…”
Section: In Perspective: An Integrative View Of the Problemmentioning
confidence: 99%